Pemahaman Hak Dan Kewajiban Warga Negara Sebagai Pilar Penguatan Karakter Bangsa - Meliwati (CV. SINAR HOWUHOWU, 2025)
This study aims to explore the understanding of Indonesian citizens regarding their rights and obligations as pillars for strengthening national character. A descriptive qualitative approach was used, with data collection techniques including in-depth interviews, focus group discussions (FGD), and observations in several locations across Indonesia. The results show that the public has a better understanding of their rights compared to their obligations. Urban communities tend to be more aware of their rights, while rural communities focus more on their obligations. However, both groups still lack understanding of the relationship between rights and obligations, which should complement each other. This study recommends improving the quality of civic education with a more practical and experiential approach, as well as the need for teacher training to deliver more engaging and contextual material. The findings are expected to contribute to the development of more effective civic education policies in Indonesia.